LAYANAN INFORMASI DENGAN TEKNIK PERMAINAN UNTUK MENINGKATKAN RASA TANGGUNG JAWAB REMAJA DI SMA KORPRI BANJARMASIN TAHUN AJARAN 2016/2017 - Sri Isna Prehesti (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2017)
The type of research used in this research is the Research Action Counseling Guidance with four. The subjects of this study were X-1 students of SMA KORPRI Banjarmasin which numbered 33 students, covering 14 women and 19 men. Data collection methods used were observations and interviews, while data analysis techniques using descriptive qualitative. The results obtained on the implementation of this service are: (1) results in the implementation of information services experience changes to information services that is information services in responsibility by through game techniques can facilitate in students' understanding of the sense of responsibility teenagers in the future after them later , (2) the result of observation in the responsibility of adolescent to the students after getting the information layout that is cycle I have improvement in student's understanding to the responsibility of adolescents categorized enough because still not awkward to memilkinya, cycle II start improvement in student understanding to teenagers responsibility categorized good because it can focus with a responsible attitude, cycle III can be an increase in student understanding responsibility remaga categorized well this is equal to cycle II result, whereas after giving action informais service on cycle IV increase in responsibility teenagers' answers are well categorized because of changes in the information services prose by using games on students in the information service. So in the service using game techniques on information services has facilitated in increasing the responsibility of adolescents to students and make information services so effective.